2014
DOI: 10.3109/14756366.2013.868599
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the δ-carbonic anhydrase from the marine diatomThalassiosira weissflogii, TweCA

Abstract: Diatom genome sequences clearly reveal the presence of different systems for HCO 3 À uptake. Carbon-concentrating mechanisms (CCM) based on HCO 3 À transport and a plastid-localized carbonic anhydrase (CA, EC 4.2.1.1) appear to be more probable than the others because CAs have been identified in the genome of many diatoms. CAs are key enzymes involved in the acquisition of inorganic carbon for photosynthesis in phytoplankton, as they catalyze efficiently the interconversion between carbon dioxide and bicarbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 38 publications
0
55
0
Order By: Relevance
“…Six different, genetically distinct CA families are known to date, the a-, b-, g-, d-, z-and Z-CAs [8][9][10][11] . The a-, b-, d-and Z-CAs use Zn(II) ions at the active site, the g-CAs are probably Fe(II) enzymes (but they are active also with bound Zn(II) or Co(II) ions), whereas the z-class uses Cd(II) or Zn(II) to perform the physiologic reaction catalysis 5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Many representatives of all these enzyme classes have been crystallized and characterized in detail, except d-and Z-CAs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six different, genetically distinct CA families are known to date, the a-, b-, g-, d-, z-and Z-CAs [8][9][10][11] . The a-, b-, d-and Z-CAs use Zn(II) ions at the active site, the g-CAs are probably Fe(II) enzymes (but they are active also with bound Zn(II) or Co(II) ions), whereas the z-class uses Cd(II) or Zn(II) to perform the physiologic reaction catalysis 5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Many representatives of all these enzyme classes have been crystallized and characterized in detail, except d-and Z-CAs.…”
Section: Introductionmentioning
confidence: 99%
“…Many representatives of all these enzyme classes have been crystallized and characterized in detail, except d-and Z-CAs. The three-dimensional analysis of CAs present a substantial variability between the different classes: the overall shape of the molecules, the protein folding patterns as well as the oligomeric organization of the six genetic CA families are very much different 5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . For example, a-CAs are normally monomers and rarely dimmers; b-CAs are dimers, tetramers or octamers; g-CAs are trimers, whereas the d-and z-CAs are less well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,[30][31][32][33][34][35][36][37][38] These enzymes are involved in a multitude of physiologic processes in organisms all over the phylogenetic tree, with six genetically distinct CA classes known to date: the a-, b-, c-, d-, f-and g-CAs. 26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type.…”
Section: Introductionmentioning
confidence: 99%
“…26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type. [55][56][57][58]60 Many such enzymes also possess biotechnologic applications for biomimetic CO 2 capture processes.…”
mentioning
confidence: 99%